2015
DOI: 10.1017/s1431927615000185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Grayscale Characteristics in Images of Labeled Microtubules from Cultured Cardiac Myocytes

Abstract: Microtubules of cardiac myocytes depolymerize after a hypoxic insult or treatment with colchicine. However, little attention has been paid to quantifying changes in microtubule distribution when using fluorescent images. We converted fluorescence images of labeled microtubules in H9C2 cardiac myocytes to grayscale images, then filtered the images to remove any noise, and used grayscale histograms to quantify features of the images. The results show that parameters such as the mean, variance, skewness, kurtosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In our study, a higher skewness (Sk > 0) value corresponds to a more heterogeneous distribution of MTs 33 .…”
Section: Methodssupporting
confidence: 50%
“…In our study, a higher skewness (Sk > 0) value corresponds to a more heterogeneous distribution of MTs 33 .…”
Section: Methodssupporting
confidence: 50%
“…We further found that SD and kurtosis based on the histogram of HE staining in the induction group were significantly higher than those of the control group. According to previous reports (20,30,31), SD (or variance or coefficients of variation) and kurtosis derived from the histopathological image were positively associated with frequency and distribution of pixels, which was presumably related to tissue heterogeneity. Therefore, our histopathological results confirmed that a low dose of sorafenib could induce a more heterogeneous HCC compared with HCC without intervention.…”
Section: Discussionmentioning
confidence: 60%
“…In accordance with our previous methods (Dang et al, 2015), microtubule image acquisition was performed using a confocal scanning microscope (TCS SP5; Leica, Wetzlar, Germany) and a 60× oil immersion objective (NA = 1.4). Cy3 was excited at 555 nm, and laser power was controlled at 50%.…”
Section: Imaging and Image Preprocessingmentioning
confidence: 99%